Expression of both poly r(C) binding protein 1 (PCBP1) and miRNA-3978 is suppressed in peritoneal gastric cancer metastasis. Issue 1 (December 2017) - Ji, Fu-jian; Wu, Yuan-yu; An, Zhe; Liu, Xue-song; Jiang, Jun-nan; Chen, Fang-fang; Fang, Xue-dong
Abstract The expression of legumain which has been shown overexpressed in patients with metastatic gastric cancer is positively correlated to both disease progression and outcome, and negatively correlated to microRNA (miR)−3978 expression. The RNA-binding protein, poly r(C) binding protein 1 (PCBP1) was the most downregulated protein in the metastatic tissue specimens. Quantitative real-time PCR showed thatPCBP1 expression is transcriptionally downregulated in peritoneal metastasis tissues. RNA immunoprecipitation experiments showed that PCBP1 and miR-3978 are sequestered in normal peritoneal tissue, but the complex is disrupted following metastatic progression.PCBP1 expression mimicked miR-3978 expression across gastric cancer patients. Finally, replenishment ofPCBP1 or miR-3978 expression in the peritoneal metastasis cell line MKN45 decreased legumain protein expression and chemosensitized the cells to treatment with docetaxel. However, replenishment of one and concomitant depletion of the other failed to induce chemosensitivity to docetaxel. Replenishment of miR-3978 also resulted in induction of PCBP1 protein expression, potentially indicating that miR-3978 expression might downregulate a negative regulator targetingPCBP1 . Our current study revealsPCBP1 as an additional biomarker in peritoneal metastasis.PCBP1 and miR-3978 expression were correlated and suggests a potential interplay of differential miRNA biogenesis and RNA binding protein during metastatic progression.